Frequency of branching pattern variation of the renal artery in a subset of Karachi population: A Study on Multi-Detector Computed Tomography - Maria Mohiuddin; Rosheena Nabeel Khan; Syeda Bushra Ahmed; Mubina Lakhani; Amatul Sughra; Nuzhat Hassan (Journal of Rawalpindi Medical College)
Abstract